Ureteral polypoid endometriosis causing hydroureteronephrosis - Kondo Takeshi (Wolters Kluwer Medknow Publications, 2009)
A 44-year-old Japanese woman presented with a left low back pain. Abdominal ultrasonography revealed the left hydroureteronephrosis. She had the past history of endometriosis interna 3 years before. Retrograde pyelography showed the defect in the ureter, and on ureteroscopy, a polypoid mass was identified. Biopsy specimen from the ureteral mass showed endometrioid epithelia and edematous endometrial stroma, immunohistochemically positive for progesterone receptor (PgR), estrogen receptor (ER), and CD 10. For the lesion (endometrioma), partial resection of the ureter and ureteroneocystostomy with Boari flap were performed. The resected specimen showed a 2-cm polypoid mass. Histologically, the lesion was ureteral endometriosis. The postoperative course was uneventful, the patient showed no evidence of local recurrence after the initial resection and continues to be under close follow up. Urinary tract involvement of endometriosis is uncommon. Endometriosis should be included in the differential diagnosis of ureteral strictures in sexually active young females.